Mortality Trends in Young People Aged 1-24 Years: Argentina, 1947-2012 - Vanessa Di Cecco; Marcio Alazraqui; Hugo Spinelli (Ubiquity Press, 2017)
Background Global mortality trends highlight changing patterns in young people, especially young men, yet little evidence of long-term trends is available in Argentina. Objective Given the lack of published evidenced within the country, this work seeks to construct long-term mortality trends for young people in Argentina. Methods A descriptive mortality time series was developed for ages 1-24 years by sex and cause of death in Argentina during 1947-2012. Diverse international and domestic public data sources were used to calculate the specific mortality rates. Causes of death were classified into the 3 Global Burden of Disease groups to ensure comparability. Findings The greatest decline in mortality was found in the 1-4 year age group. Women and girls of all ages had large decreases in mortality. Mortality in boys and men aged 15-24 years declined, but much less than in all other groups; mortality in this group was twice that of women and girls by 2012. Mortality as a result of communicable, nutritional, and maternal causes declined in all groups, but in young men injury mortality increased. In all groups, reductions were greater during the first half of the period. Conclusions Long-term trends offer a broader view of health phenomena-like injury mortality, disproportionately affecting young men-so as to better inform actions and policy that could change ways of living and dying in Argentina.